LEARNING PROCESS AND CONSTRAINTS OF STUDENTS OF SMP NEGERI 1 RANTAU UTARA IN THE COVID-19 PANDEMIC YEAR 2021/2022 ANALYSIS OF STUDENT RESPONSE - Kurnia Putra; Irham Huspa K. Siregar (Jurnal Scientia, 2022)
This study aims to analyze the process and activity constraints during online learning during the COVID-19 pandemic based on student responses. This type of research is descriptive qualitative. The data collection was carried out by distributing a Google form containing 15 questions to students from grades VII-IX. The results of this study indicate that the online learning process is running quite well. Some of the obstacles are the difficulty of understanding online learning. The learning process still needs to be optimized and evaluated in order to get satisfactory results and improvements.